The effect of ergogenic substances on liver function in athletes – a literature review - Dubniański, Bartosz; Fudali, Kacper; Hejnowicz, Mateusz; Tymec, Jan; Wajerowska , Weronika; Nawracaj , Barbara; Browarny, Sonia; Stawińska, Kornelia (Quality in Sport, 2026)
Introduction Athletes commonly use ergogenic substances, ranging from natural to pharmacological agents, aiming to enhance their performance. This review analyses their risks in terms of hepatotoxicity and liver health. Materials and Methods A thorough research was conducted using the following databases: Embase, PubMed, Cochrane Library, and Google Scholar, in accordance with PRISMA guidelines. The keyword choice was decided based on the subject of the review beforehand. The Stage of Knowledge The review subsumes anabolic-androgenic steroids (AAS), selective androgen receptor modulators (SARMs), creatine, caffeine and herbal supplements. Despite strict bans, AAS and SARMs are widely abused, also among youth. Many of them display serious adverse effects, including consecutive signs of liver damage culminating in drug-induced liver injury (DILI). Moreover, SARMs present severe testosterone suppression. Overall, the safety profile of exogenous creatine is good and non-hepatoxic. The reports of serious side effects remain anecdotal. Additionally, there is a rising number of reports on the therapeutic application of creatine, also in terms of the liver. Caffeine effectively enhances endurance and glycogen recovery. Green tea, rich in catechins, minimises exercise induced muscle-damage and, by lowering AST levels and reducing oxidative stress, actively protects the liver. Both maintain a favourable safety profile. Summary Ultimately, the impact of ergogenic substances on liver health ranges from highly toxic to safe, even beneficial, within a broad spectrum. This contrast highlights the critical need for athletes to consider the severe adverse effects of any illicit and harmful substances against those proven to be both safe and effective. It is all in terms of their own well-being and the trends that later spread among people they are being looked up to.